2016
DOI: 10.1007/s12079-016-0335-9
|View full text |Cite
|
Sign up to set email alerts
|

Different expression and subcellular localization of Phosphoinositide-specific Phospholipase C enzymes in differently polarized macrophages

Abstract: Macrophages' phenotypic and functional diversity depends on differentiating programs related to local environmental factors. Recent interest was deserved to the signal transduction pathways acting in macrophage polarization, including the phosphoinositide (PI) system and related phospholipase C (PLC) family of enzymes. The expression panel of PLCs and the subcellular localization differs in quiescent cells compared to the pathological counterpart. We analyzed the expression of PLC enzymes in unpolarized (M0), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 53 publications
2
25
0
2
Order By: Relevance
“…Previous studies indicated that PLC γ isoforms are involved in the inflammatory activation of macrophages (Di Raimo et al 2016). PLC γ subfamily is activated in the presence of AA that serves as a common link between receptor activation of Phospholipase A2 and the PI pathway (Suh et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies indicated that PLC γ isoforms are involved in the inflammatory activation of macrophages (Di Raimo et al 2016). PLC γ subfamily is activated in the presence of AA that serves as a common link between receptor activation of Phospholipase A2 and the PI pathway (Suh et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that in the case of human macrophages (derived from peripheral blood mononuclear cells), PLC β 1–4, γ 1-2, δ 1, and η 1-2 are expressed in unstimulated macrophages, PLC β 1–3, γ 1-2, δ 1 and 3, and η 1-2 are expressed in M1 macrophages, and PLC β 1–3, γ 1-2, δ 3, and η 1-2 are expressed in M2 macrophages. In addition, these PLC isoforms showed different subcellular localization in differently polarized macrophages [ 46 ]. The distinct expression spectrum and subcellular localization of these PLC isoforms reflect the diverse roles that they play in the regulation of the inflammatory response.…”
Section: The Spectrum Of Expression Of Plc Isoenzymes In Macrophagmentioning
confidence: 99%
“…In particular, PI-PLCβ2 and PI-PLCβ3 isozymes play a crucial role in inhibiting the switch from M1 to M2 phenotype [ 24 , 25 ], and lipids generated by iPLA 2 β favor M1 polarization [ 26 ]. In addition, differently polarized macrophages were shown to own peculiar panels of expression and intracellular localization of PI-PLC enzymes, which slightly change following triggering with inflammatory stimuli [ 27 ].…”
Section: Macrophage and Phospholipase Biologymentioning
confidence: 99%